Reimagining Student Evaluation of Teaching: Student-Perceived Factors of Effective Teaching in Higher Education - Dinamling, Shayne Klarisse; Depaynos, Jonas (Journal of Interdisciplinary Perspectives, 2025)
This study explores key dimensions of effective teaching in higher education through student evaluations. Amidst increasing competition among higher education institutions and growing emphasis on the teaching-learning process, Student Evaluations of Teaching (SETs) are seen as tools to enhance institutional competitiveness. However, current SET tools often lack student-centered elements, leading to a disconnect between educators’ and learners' understandings of quality instruction. This research addresses this gap by investigating student perspectives on teaching effectiveness. The study, conducted at a private higher education institution in the Philippines, involved 276 sophomore students in the Teacher Education program. A modified survey tool, developed from existing SET instruments and refined through expert review, was used to gather data. Exploratory Factor Analysis was employed to identify underlying dimensions of effective teaching. The analysis revealed three primary dimensions: Transformative and Critical Pedagogical Practices, Optimized Learning Support and Resources, and Ethical Conduct and Socio- Emotional Intelligence. These dimensions underscore the significance of student engagement, resource utilization, and interpersonal dynamics in the teaching and learning process. The study suggests a student- centric SET framework incorporating these dimensions to provide actionable insights for improving teaching practices. The findings underscore the importance of institutions prioritizing responsive and critical pedagogies, effective resource management, and cultivating value systems to empower learners and foster a more inclusive and responsive learning environment.